Prevalence and Pattern of Substance Use among Secondary School Students in the Colombo District - AC Ismail; R De A Seneviratne (College of Community Physicians of Sri Lanka, 2011)
Aims This study seeks to determine prevalence and pattern of substance use among school-going adolescents in the Colombo district. Methodology Cross-sectional survey was conducted among 3454, 13-18 year-old adolescents from 29 schools selected proportionate to size using multi-stage cluster sampling. Validated Sinhala Adolescent Substance Use Student Questionnaire (ASUSQ) assessed: cigarettes, alcohol, marijuana, other drug use; age at first use; substance, source and place of first use; consequences and reasons for use and non-use. A standardised procedure was used to collect data. Analytical strategies eliminated returned questionnaires of questionable validity. Results Sixteen percent (n=512) of adolescents had used at least one substance during their life. Prevalence of lifetime and current cigarette, alcohol, marijuana and other drug use were: 6.1% and 1.7%, 13.6% and 2.2%, 2% and 0.7%, and 1% and 0.1%, respectively. Significantly more males than female adolescents reported substance use. Substance use increased with age. Substance of first use was alcohol. Source and place of first use was friends and social gathering, respectively. Age at first use and the lowest age at first use varied with substance. Conclusions Lifetime and current prevalence, and frequency of substance use indicated that a majority of users were experimenters. Use of a validated instrument and standardised procedure improved accuracy of prevalence estimates in this study. Key Words: Adolescent substance use; prevalence of substance use; Sinhala Adolescent Substance Use Student Questionnaire (ASUSQ); school-going adolescents DOI: 10.4038/jccpsl.v13i2.2964 Journal of the College of Community Physicians of Sri Lanka Vol.13(2) 2008 17-25